Emerging protein kinase inhibitors for non-small cell lung cancer. (March 2014) - Liu, Stephen V; Subramaniam, Deepa; Cyriac, George C; Abdul-Khalek, Feras J; Giaccone, Giuseppe
<x xml:space="preserve">Abstract</x> Introduction: In the current paradigm of precision medicine in non-small cell lung cancer (NSCLC), the therapeutic strategy is determined by the molecular characteristics. The best examples of this approach are the kinase inhibitors that selectively target tumors bearing an epidermal growth factor receptor (EGFR) mutation or an anaplastic lymphoma kinase (ALK) rearrangement. Emerging protein kinase inhibitors may enhance our ability to effectively treat these and other genomic subtypes of NSCLC. Areas covered: This article reviews the next-generation kinase inhibitors targeting EGFR and ALK-positive NSCLC. In addition, targeted kinase inhibitors in clinical development for other specific molecular subtypes of NSCLC are covered, including ROS1, BRAF, RET, HER2, KRAS (upstream of the MEK kinase), MET, PIK3CA, FGFR1, DDR2, VEGFR and AAK. Expert opinion: In EGFR-mutant NSCLC, there are several kinase inhibitors with promising activity, most notably dacomitinib and CO-1686 in tumors with acquired resistance to EGFR-targeted therapy. Next-generation ALK inhibitors appear to have greater potency than crizotinib and several ongoing trials may shed light on their role in both ALK- and ROS1-positive NSCLC. While there is optimism regarding the role of kinase inhibitors in other molecular subtypes, the available evidence is too immature to make recommendations and results from prospective trials are needed.